The application of the audiovisual media snowball throwing model to improve students' ability to write narrative text (Research, Society and Development, 2020)
This research objective is to find out the significant effect of the Snowball Throwing model with audiovisual media on the ability to write narrative text of UMN English Education Students of UMN Al-Washliyah. The research subjects were English Education FKIP students. There were about 22 students who participated in the research using a Quasi Experimental Design research approach. This study used a pretest and posttest control group design. Based on the statistical output, it is found that the average score for the improvement of students' narrative text writing skills or the mean for the control class is 0.19486 which belongs to the low increase category, while for the experimental class it is 0.36691 which belongs to the moderate improvement category. Thus, statistically and descriptively,  it can be said that there is a difference in the average score for the improvement of students' narrative text writing skills between the control class and the experimental class. Based on the Independent Samples Test output table in the Equal variances assumed section, the Sig. (2-tailed) of 0.008 which is smaller than 0.05, so it can be concluded that there is a significant difference between the average value of the improvement in students' narrative text writing skills between the control class and the experimental class. Furthermore, the Mean Difference value obtained is -0.172041, which means that the difference between the average value of the increase in students' narrative text writing skills in the control class and the experimental class is 0.172041. From the description above, as a conclusion, learning with audiovisual based animation media is better at improving students' narrative text writing skills.